Using properties of determinants, prove that:
$\left|\begin{array}{ccc}3 a & -a+b & -a+c \\ -b+a & 3 b & -b+c \\ -c+a & -c+b & 3 c\end{array}\right|=3(a+b+c)(a b+b c+c a)$
$\Delta=\left|\begin{array}{ccc}3 a & -a+b & -a+c \\ -b+a & 3 b & -b+c \\ -c+a & -c+b & 3 c\end{array}\right|$
Applying $C_{1} \rightarrow C_{1}+C_{2}+C_{3} .$ We have:
$\Delta=\left|\begin{array}{ccc}a+b+c & -a+b & -a+c \\ a+b+c & 3 b & -b+c \\ a+b+c & -c+b & 3 c\end{array}\right|$
$=(a+b+c)\left|\begin{array}{ccc}1 & -a+b & -a+c \\ 1 & 3 b & -b+c \\ 1 & -c+b & 3 c\end{array}\right|$
Applying $R_{2} \rightarrow R_{2}-R_{1}$ and $R_{3} \rightarrow R_{3}-R_{1},$ we have:
$\Delta=(a+b+c)\left|\begin{array}{ccc}1 & -a+b & -a+c \\ 0 & 2 b+a & a-b \\ 0 & a-c & 2 c+a\end{array}\right|$
Expanding along $C_{1},$ we have:
$\Delta=(a+b+c)[(2 b+a)(2 c+a)-(a-b)(a-c)]$
$=(a+b+c)\left[4 b c+2 a b+2 a c+a^{2}-a^{2}+a c+b a-b c\right]$
$=(a+b+c)(3 a b+3 b c+3 a c)$
$=3(a+b+c)(a b+b c+c a)$
Hence, the given result is proved.
For a non - zero, real $a, b$ and $c$ $\left| {\begin{array}{*{20}{c}}{\frac{{{a^2} + {b^2}}}{c}}&c&c\\a&{\frac{{{b^2} + {c^2}}}{a}}&a\\b&b&{\frac{{{c^2} + {a^2}}}{b}} \end{array}} \right|$ $= \alpha \, abc$, then the values of $\alpha$ is
Prove that $\left|\begin{array}{ccc}a & a+b & a+b+c \\ 2 a & 3 a+2 b & 4 a+3 b+2 c \\ 3 a & 6 a+3 b & 10 a+6 b+3 c\end{array}\right|=a^{3}$
Evaluate $\Delta=\left|\begin{array}{lll}1 & a & b c \\ 1 & b & c a \\ 1 & c & a b\end{array}\right|$
Evaluate $\left|\begin{array}{ccc}102 & 18 & 36 \\ 1 & 3 & 4 \\ 17 & 3 & 6\end{array}\right|$
The number of positive integral solutions of the equation $\left| {\begin{array}{*{20}{c}}{{x^3} + 1}&{{x^2}y}&{{x^2}z}\\{x{y^2}}&{{y^3} + 1}&{{y^2}z}\\{x{z^2}}&{y{z^2}}&{{z^3} + 1}\end{array}} \right|$ $= 11$ is